Body weight in relation to hours of sleep, and physical activity in Latin American university students during the Covid-19 pandemic - Meza Miranda, Eliana Romina (2022)
Introduction: Short sleep, physical inactivity, and being locked up are risk factors for weight gain. Objective: We evaluated weight gain according to sex, age, hours of sleep and physical activity in university students from 10 Latin American countries during the COVID-19 pandemic. Methods: Cross-sectional and multicenter study (n=4880). Results: The average age was 22.5±4.4 years. 60.2% were currently locked up. 73.6% were women, 48.2% increased their body weight, 66% reported insufficient sleep hours, and 65.9% were inactive. Women gained more weight than men (73.2%) and younger students gained more weight (85.1%). Those who had insufficient sleep hours gained most weight (67.6%). Inactive participants gained most weight (74.7%). Students who have insufficient sleep are 21% more likely to have changes in body weight compared to students who have optimal sleep. Conclusion: The increase in body weight and its risk factors during confinement should be considered as emerging from public health.